Social Media and Patient Health Outcomes - Staccini, P.; Douali, N.; Section Editors for the IMIA Yearbook Section on Consumer Health Informatics (Yearbook of Medical Informatics, 2014)
Objectives: To provide a review of the current excellent research published in the field of Consumer Health Informatics.Method: We searched MEDLINE® and WEB OF SCIENCE® databases for papers published in 2013 in relation with Consumer Health Informatics. The authors identified 16 candidate best papers, which were then reviewed by four reviewers.Results: Five out of the 16 candidate papers were selected as best papers. One paper presents the key features of a system to automate the collection of web-based social media content for subsequent semantic annotation. This paper emphasizes the importance of mining social media to collect novel data from which new findings in drug abuse research were uncovered. The second paper presents a practical method to predict how a community structure would impact the spreading of information within the community. The third paper presents a method for improving the quality of online health communities. The fourth presents a new social network to allow the monitoring of the evolution of individuals’ health status and diagnostic deficiencies, difficulties or barriers in rehabilitation. The last paper reports on teenage patients’ perception on privacy and social media.Conclusion: Selected papers not only show the value of using social media in the medical field but how to use these media to detect emergent diseases or risks, inform patients, promote disease prevention, and follow patients’ opinion on healthcare resources.
Keywords: Social media; epidemiology; substance-related disorders; patients rights; health communities